Reaktualisasi Teologi Pluralis Untuk Ketenangan Hidup Masyarakat Perkotaan (Urban): Kajian Studi Meditasi Anapanasati Di Vihara Karangdjati Kec. Mlati, Kab. Sleman Yogyakarta - Ulfah, Khoiriya; Sari, Riski Mayang; Nabila, Mutia Ainun; Badruzaman (AL-ADYAN, 2025)
The purpose of this article is to explore the importance of pluralist theology for the serenity of urban society in the study of anapanasati meditation in the Karangdjati monastery. The subjects of the study were non-Buddhist meditation participants, meditators and administrators of Karangdjati Vihara. Anapanasati meditation (breathing meditation) at Karangdjati Vihara is increasingly practiced by people who adhere to different religions or have different ways of worship, especially non-Buddhist participants. The results of this study show that there are several Reactualizations of pluralist theology, namely that meditation not only serves as a spiritual practice that allows individuals to focus on themselves and understand the universal values embraced by various religions and cultures, but also as a process that facilitates understanding and appreciation of other religious and cultural differences. Therefore, meditation in the context of pluralist theology helps individuals gain a deeper awareness and understanding of the universal values upheld by different religions and cultures, while also helping to reduce conflict and encourage interfaith and intercultural dialogue.